Executive Functions and Social Responsiveness in Children and Adolescents With Autism Spectrum Disorder and Attention Deficit Hyperactivity Disorder - PERDAHLI FİŞ, NEŞE (AVES, 2021)
Objective: To evaluate the executive functions and social reciprocity of children and adolescents diagnosed with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) and compared them with healthy controls. Material and Method: Patients aged 6-17 years diagnosed with ASD (n=33) and ADHD (n=37) and healthy controls in the same age range (n=33) were included in the study. Behavioral Rating Inventory of Executive Functions (BRIEF) sub-scales and Social Responsiveness Scale (SRS) were used for evaluating executive function areas and social responsiveness. Results: Our results revealed that children and adolescents with ASD and ADHD were significantly impaired for all BRIEF sub-scales except emotional control and that the significant increase in sub-scale scores expressing deterioration continued after adjustment for SES, verbal IQ scores, and gender. ASD patients received significantly higher SRS scores compared to ADHD and control groups and ADHD patients also had significantly higher values compared to the controls. Conclusion: Further studies with parent-report scales that allow easier and faster evaluation of executive functions and social reciprocity will contribute to better understanding of the personal needs of children with neurodevelopmental disorders and the finding of new treatments.
Keywords: Autism; ADHD; executive function; social responsiveness; SRS; BRIEF; DEFICIT/HYPERACTIVITY DISORDER; TURKISH VERSION; PROFILES